A nation of bureaucrats or a nation of workers? Welfare benefits as nation-building modernization tools in interwar Romania. (February 2022) - Delcea, Sergiu
As one of the most potent hypothesis in political economy, the negative impact of ethnic diversity on the provision of public goods made the welfare state–nation state isomorphism seem a one-way connection. Against the grain of existing studies I argue, through a case-study of interwar Romania, that welfare states are constructed to proactively (re)build the nation, rather than retroactively emanate from it, once established. Rather than an ahistorical ethnolinguistic fractionalization, the article takes nationhood as historically fluid and contested because through institutionalized action, elites can and do proactively revamp the political arena, redistributing coalitions of winners and losers based on exogenously given criteria. The article therefore shows that nation forgers typically internalize the global social question through the topoi of local socio-economic problems construed as a national question. Because elites can pick and choose who becomes part of the national compact, the politicization of the perception of incomplete nationhood provides a sufficient ideational thrust for welfare policymaking, irrespective of pre-existing national solidarities. Consequently, welfare policies are typically layered as remedial or compensatory policies designed to foster a specific social mobility, deemed in a top-down fashion to be completing the nation.